Whither the Study of Religion and Culture? - Newton, Richard (Implicit religion, 2017)
A speech is presented by Richard Newton at the Elizabethtown College. Topics discussed include sociology and philosophy of religion; views of Malory Nye on religion; and Teemu Taira's look at the religious studies. It also mentions about impact of human activities, interests and categories on religion.